Mechanisms underlying the protective effects of blueberry extract against ultraviolet radiation in a skin cell co-culture system. (January 2019) - Wang, Huailing; Liu, Jie; Pang, Daorui; Li, Tong; Liu, Rui Hai
Graphical abstract: Highlights: BE could protect HaCaT and HFF cells against UVC irradiation. MMP-1 contents were increased in HFF cells after UVC irradiation. BE could inhibit inflammation gene. BE partly recovered the expression of protein MMP-1, c-fos, c-jnu in MAPK pathways. Abstract: Ultraviolet radiation induces skin damage, inflammation, and aging. To explore the protective effects of blueberry extract (BE) against ultraviolet-C (UV-C) radiation, we analysed human skin keratinocyte (HaCaT) and human foreskin fibroblast (HFF) cells alone or in a co-culture, treated or not with BE, after exposure to UV-C. Surprisingly, MMP-1 was significantly up-regulated in HFF cells and in the co-cultured cell group in response to UV-C irradiation (8 mJ/cm 2 ), but not in HaCaT cells. As expected, BE had a significantly protective effects; it decreased DNA fragmentation and inhibited MMP-1 and inflammatory factors expression in response to UV-C radiation. In addition, BE reduced the accumulation of proteins (MMP-1, c-fos, and c-jnu) in the MAPK (mitogen-activated protein kinase) pathway after UV-C radiation. Taken together, these results showed that BE exerted a protective effect against UV-C irradiation, and modulated MMP-1 production through MAPK signalling by direct and indirect pathways in HaCaT and HFF cells.